Change in fishing performance of tubular pot for conger eels according to the angle of inclination to seabed - Kim, Seonghun; Kim, Pyungkwan; Jeong, Seongjae; Lee, Kyounghoon; Oh, Wooseok (Indian Journal of Fisheries, 2019)
An experiment was conducted to investigate the fishing performance of tubular pots for conger eel in South Korea according to the inclination angle on the seabed. The experiment was conducted in a water tank by setting the angle of the tubular pot at 0°, 15°, 30°, 45° and 60° with respect to the bottom level. When the landing angle of the pot was relatively low, conger eels searched for the bait and focused on where the bait smell was being released. Subsequently, conger eels entered the pot. Thus, for catching conger eels, it is advantageous for the bait to be placed at the entrance side while installing the pot. The highest fishing performance in terms of catch per unit effort (CPUE) was at an inclination angle of 15°. There was a significant difference between the CPUEs and the landing angle (Kruskal-Wallis test, p = 0.009). The results of this study could be used to improve the efficiency of tubular pot operations for conger eels. Keywords: Conger eel, Fish behaviour, Fishing performance, Landing angle, Tubular pot